Disentangling the nature of the first radio weak BL Lac: Contemporaneous multifrequency observations of WISE J141046.00+740511.2 - Marchesini, Ezequiel Joaquín (2022)
Context. The gamma-ray emitting source WISE J141046.00+740511.2 has been associated with a Fermi-LAT detection by crossmatching with Swift/XRT data. It has shown all the canonical observational characteristics of a BL Lac source, including a power-law, featureless optical spectrum. However, it was only recently detected at radio frequencies and its radio flux is significantly low. Aims. Given that a radio detection is fundamental to associate lower-energy counterparts to Fermi-LAT sources, we aim to unambiguously classify this source by performing a multiwavelength analysis based on contemporaneous data. Methods. By using multifrequency observations at the Jansky Very Large Array, Giant Metrewave Radio Telescope, Gran Telescopio Canarias, Gemini, William Herschel Telescope and Liverpool observatories, together with Fermi-LAT and Swift data, we carried out two kinds of analyses. On one hand, we studied several known parameters that account for the radio loudness or weakness characterization and their application to blazars (in general) and to our source (in particular). And, on the other hand, we built and analyzed the observed spectral energy distribution (SED) of this source to try to explain its peculiar characteristics. Results. The multiwavelength analysis indicates that WISE J141046.00+740511.2 is a blazar of the high-frequency peaked (HBL) type that emits highly polarized light and that is likely located at a low redshift. In addition, the one-zone model parameters that best fit its SED are those of an extreme HBL (EHBL); this blazar type has been extensively predicted in theory to be lacking in the radio emission that is otherwise typical of canonical gamma-ray blazars. Conclusions. We confirm that WISE J141046.00+740511.2 is indeed a highly polarized BL Lac of the HBL type. Further studies will be conducted to explain the atypical low radio flux detected for this source.